Profile control agent and application thereof

By introducing cellulose ether and a second sealing agent into the dispensing agent, and using its high temperature resistance and strong sealing properties, the problem of existing dispensing agents being difficult to seal deep is solved, and the high-strength sealing and oil-enhancing effect of steam-driving deep is improved.

CN119823735AActive Publication Date: 2025-04-15PETROCHINA CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311327138.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-15
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

The existing profile adjusting agents are difficult to carry solid phase particles to the deep oil layer, resulting in poor sealing effect in the deep steam drive radius and poor oil increase effect.

Method used

A new type of dissection modulating agent is used, and its raw material components include cellulose ether, a first sealing agent, a thickening agent, a crosslinking agent, a heat stabilizer and a second sealing agent. The second sealing agent is composed of ligno fiber, starch and resin, and has different particle sizes combined with the first sealing agent to form a high temperature resistant and strong sealing glue-forming system.

Benefits of technology

High-strength sealing in the large pores of steam-driving formation and high permeability deep areas has been achieved, the steam absorption profile of the oil layer is improved, the oil increase effect is enhanced, and good temperature resistance and long-term sealing ability are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823735A_ABST
    Figure CN119823735A_ABST
Patent Text Reader

Abstract

The invention relates to a profile control agent and application thereof, raw material components comprise a first blocking agent, a thickening agent, a cross-linking agent and a heat stabilizer, and the raw material components further comprise cellulose ether and a second blocking agent; wherein the raw material components of the second blocking agent comprise lignin fibers, starch and resin, and the second blocking agent and the first blocking agent have different particle sizes. The technical problem that an existing profile control agent is difficult to carry solid-phase particles to the deep part of an oil layer is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of oil production, and in particular to a profile control agent and application thereof. Background Art

[0002] Steam drive has entered the middle and late stages of development. Affected by factors such as reservoir heterogeneity, formation dip, sedimentary phase, steam overlap, and the inability to dynamically adjust the injection process, steam has broken through the main layer, forming a dominant channel between the injection and production wells, and the production wells have serious steam channeling, which manifests as high temperature, high liquid, and high water content. The injected steam circulates inefficiently and ineffectively, while the steam utilization in non-main layers and non-main directions is poor.

[0003] At present, it is difficult for polyacrylamide gel profile control agents to carry solid particles to deep oil layers for plugging, and they cannot meet the requirements of long-radius deep plugging in steam drive. Steam is prone to bypass, resulting in poor profile control and oil production increase effects and a short effective period. Summary of the invention

[0004] The present application provides a profile control agent and application thereof, so as to solve the technical problem that the existing profile control agents are difficult to carry solid phase particles to the deep oil layer.

[0005] In a first aspect, the present application provides a profile control agent, the raw material components of which include a first plugging agent, a thickener, a cross-linking agent, and a thermal stabilizer, wherein the raw material components further include cellulose ether and a second plugging agent; wherein,

[0006] The raw material components of the second plugging agent include lignin fiber, starch and resin.

[0007] The second plugging agent has a different particle size from the first plugging agent.

[0008] Optionally, the cellulose ether includes one of the following: hydroxypropyl cellulose ether, hydroxyethyl cellulose ether, and hydroxybutyl cellulose ether.

[0009] Optionally, the resin includes one of the following: modified furfural resin, polyurethane.

[0010] Optionally, the particle size of the second plugging agent is 1.5 mm to 3 mm.

[0011] Optionally, the weight ratio of the lignin fiber, the starch and the resin is (55-65):(15-25):(15-25).

[0012] Optionally, the particle size of the first plugging agent is 0.2 mm to 2 mm.

[0013] Optionally, the content of the cellulose ether is 1.0% to 1.5% by mass.

[0014] Optionally, the content of the second plugging agent is 2% to 3% by mass.

[0015] Optionally, in terms of mass fraction, the content of the first plugging agent is 6% to 8%, the content of the thickener is 0.2% to 0.3%, the content of the cross-linking agent is 0.2% to 0.3%, and the content of the thermal stabilizer is 0.1% to 0.15%.

[0016] In a second aspect, the present application provides an application of the profile control agent described in any embodiment of the first aspect in steam drive production.

[0017] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0018] The profile control agent provided in the embodiment of the present application, the cellulose ether undergoes a polymerization reaction with a thickener, a cross-linking agent and a thermal stabilizer in the formation to form a gelling system, and the gelling system has the advantages of good temperature resistance, adjustable gelling time and high plugging strength.

[0019] In the raw material components of the second plugging agent, lignin fiber improves the plugging strength of the second plugging agent, starch has a bonding effect, and bonds the lignin fibers together, and the resin coating is wrapped on the surface of the bonded lignin fiber to improve the temperature resistance of the second plugging agent. Through the synergistic effect of lignin fiber, starch and resin, the second plugging agent has both high plugging strength and high temperature resistance; the second plugging agent has different particle sizes from the first plugging agent, and achieves deep high-strength plugging of large pores and high permeability of steam-driven formations, and improves the steam absorption profile of the oil layer. Therefore, by introducing cellulose ether and the second plugging agent into the raw material components of the profile control agent, the technical problem that the existing profile control agent is difficult to carry solid phase particles to the deep oil layer is solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 This is an apparent diagram of a second plugging agent provided in an embodiment of the present application. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0025] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0027] In a first aspect, the present application provides a profile control agent, the raw material components of which include a first plugging agent, a thickener, a cross-linking agent, and a thermal stabilizer, wherein the raw material components further include cellulose ether and a second plugging agent; wherein,

[0028] The raw material components of the second plugging agent include lignin fiber, starch and resin.

[0029] The second plugging agent has a different particle size from the first plugging agent.

[0030] In the embodiments of the present application, cellulose ether undergoes polymerization reaction with thickener, cross-linking agent and thermal stabilizer in the formation to form a gelling system, which has the advantages of good temperature resistance, adjustable gelling time and high plugging strength; in the raw material components of the second plugging agent, lignin fiber improves the plugging strength of the second plugging agent, starch has a bonding effect, and bonds the lignin fibers together, and the resin is coated on the surface of the bonded lignin fibers to improve the temperature resistance of the second plugging agent. Through the synergistic effect of lignin fiber, starch and resin, the second plugging agent has both high plugging strength and high temperature resistance; the second plugging agent has a different particle size from the first plugging agent, which realizes deep and high-strength plugging of large pores and high permeability in steam-driven formations, and improves the steam absorption profile of the oil layer. Among them, the second plugging agent prevents particles from entering the deep formation, improves the plugging strength of the near-wellbore zone, and the appearance diagram of the second plugging agent, please refer to Figure 1 , which are white particles; the first plugging agent realizes deep plugging of the formation.

[0031] In addition, the first plugging agent is used to improve the strength of the gelling system and the temperature resistance of the profile control agent to achieve deep plugging of the formation. Specifically, the first plugging agent can be plant fiber and rubber powder; wherein the raw material components of the plant fiber can include bark powder, rubber powder and rice husk powder. The thickener is used to increase the initial viscosity of the gelling system to prevent the solid particles in the profile control system from settling in the wellbore or near-wellbore area. Specifically, the thickener can be polyacrylamide, polyvinyl alcohol, polyethylene oxide, and further, polyacrylamide with a molecular weight of 18 million to 23 million and a hydrolysis degree of 20% to 25% can be preferred. The cross-linking agent is used to react with other raw material components to generate a steam-driven deep profile control agent. Specifically, the cross-linking agent can be a phenolic resin or an organic chromium cross-linking agent. The phenolic resin can be an oil-soluble phenolic resin or a water-soluble phenolic resin, preferably a water-soluble phenolic resin. The heat stabilizer is used to improve the temperature resistance of the gelling system. Specifically, the heat stabilizer can be a silane coupling agent, thiourea, or sodium sulfite.

[0032] The raw material component of the above-mentioned profile control agent also includes water, and the water includes at least one of the following: clean water, shallow layer water and oilfield produced wastewater. Preferably, the water can be oilfield produced wastewater.

[0033] In some embodiments, the cellulose ether includes one of the following: hydroxypropyl cellulose ether, hydroxyethyl cellulose ether, and hydroxybutyl cellulose ether.

[0034] In the examples of the present application, hydroxypropyl cellulose ether, hydroxyethyl cellulose ether, and hydroxybutyl cellulose ether are selected as cellulose ethers, which can improve the temperature resistance of the gelling system. Preferably, the cellulose ether can be hydroxypropyl cellulose ether, and the molecular weight can be 80,000 to 120,000, while ensuring the initial viscosity of the profile control agent and the strength of the gel.

[0035] In some embodiments, the resin includes one of the following: modified furfural resin, polyurethane.

[0036] In the examples of the present application, modified furfural resin and polyurethane are selected as resins to improve the temperature resistance of the second plugging agent to above 260° C. Considering the cost, polyurethane is preferred.

[0037] In some embodiments, the particle size of the second plugging agent is 1.5 mm to 3 mm.

[0038] In the embodiment of the present application, the particle size of the second plugging agent is controlled to improve the plugging strength of the near-wellbore zone. If the particle size of the second plugging agent is too high, it will cause the perforation hole to be blocked to a certain extent; if the particle size of the second plugging agent is too low, it will affect the plugging strength of the near-wellbore zone to a certain extent. Specifically, the particle size of the second plugging agent can be 1.5mm, 1.7mm, 1.9mm, 2.1mm, 2.3mm, 2.5mm, 2.7mm, 2.9mm, 3.0mm, etc.

[0039] In some embodiments, the weight ratio of the lignin fiber, the starch and the resin is (55-65):(15-25):(15-25).

[0040] In the embodiment of the present application, the ratio of lignin fiber, starch and resin is controlled to ensure the wrapping effect of lignin fiber and the strength of the second plugging agent. If the content of lignin fiber is too much, the integrity of the particles will be reduced to a certain extent. If the content of lignin fiber is too low, the strength of the second plugging agent will be reduced to a certain extent; if the content of starch is too much, the particle strength will be reduced to a certain extent; if the content of starch is too low, the adhesion to lignin fiber will be poor to a certain extent; if the content of resin is too much, the cost will be increased to a certain extent; if the content of resin is too low, the wrapping of lignin fiber will be reduced to a certain extent, which is not conducive to forming an effective plugging wall. Specifically, the weight ratio of lignin fiber, starch and resin can be 55:25:20, 60:20:20, 65:15:20, 60:25:15, etc.

[0041] In some embodiments, the particle size of the first plugging agent is 0.2 mm to 2 mm.

[0042] In the embodiment of the present application, the particle size of the first plugging agent is controlled to achieve deep plugging of the formation. If the particle size of the first plugging agent is too high, the plugging agent will not be able to enter the deep formation to a certain extent; if the particle size of the first plugging agent is too low, it will not have a plugging effect to a certain extent. Specifically, the particle size of the first plugging agent can be 0.2mm, 0.4mm, 0.6mm, 0.8mm, 1.0mm, 1.2mm, 1.4mm, 1.6mm, 1.8mm, 2mm, etc.

[0043] In some embodiments, the content of the cellulose ether is 1.0% to 1.5% by mass.

[0044] In the embodiments of the present application, an appropriate amount of cellulose ether is used to obtain an ideal gel strength; if the content of the cellulose ether is too high, the gel time will be shortened to a certain extent, increasing the cost; if the content of the cellulose ether is too low, the gel strength will be reduced to a certain extent. Specifically, the content of the cellulose ether can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.

[0045] In some embodiments, the content of the second plugging agent is 2% to 3% by mass.

[0046] In the embodiment of the present application, the content of the appropriate amount of the second plugging agent ensures long-term effective plugging of the near-wellbore zone; if the content of the second plugging agent is too high, it will cause formation blockage to a certain extent, making it difficult to inject; if the content of the second plugging agent is too low, it will affect the plugging strength of the near-wellbore zone to a certain extent. Specifically, the content of the second plugging agent can be 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, etc.

[0047] In some embodiments, by mass fraction, the content of the first plugging agent is 6% to 8%, the content of the thickener is 0.2% to 0.3%, the content of the cross-linking agent is 0.2% to 0.3%, and the content of the thermal stabilizer is 0.1% to 0.15%.

[0048] In the embodiment of the present application, an appropriate amount of the first plugging agent is used to ensure effective plugging of the deep formation; an appropriate amount of the thickener is used to control the initial viscosity of the gel; an appropriate amount of the cross-linking agent is used to control the gelling strength of the gel; and an appropriate amount of the thermal stabilizer is used to improve the temperature resistance of the gel system. Specifically, the content of the first plugging agent can be 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7%, 7.2%, 7.4%, 7.6%, 7.8%, 8% and the like, the content of the thickener can be 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3% and the like, the content of the cross-linking agent can be 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3% and the like, the content of the heat stabilizer can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15% and the like.

[0049] The preparation method of the above-mentioned profile control agent comprises: adding weighed thickener, crosslinking agent, heat stabilizer and cellulose ether into sewage, stirring for 20 minutes to obtain a mixture; adding a first plugging agent and a second plugging agent into the above-mentioned mixture, stirring for 25 minutes to obtain a profile control agent.

[0050] In a second aspect, the present application provides an application of the profile control agent described in any embodiment of the first aspect in steam drive production.

[0051] The profile control agent provided in the embodiments of the present application has at least the following beneficial effects:

[0052] (1) The profile control agent has good temperature resistance, which can reach above 300°C, meeting the long-term high-temperature plugging requirements of steam flooding;

[0053] (2) The gelling temperature of the profile control agent is 70°C to 120°C, and the gelling time is 12 to 48 hours. The gelling time is long and adjustable, and the shear resistance is strong. It meets the requirements of long-term injection and long-distance migration of steam drive profile control agents, and can achieve deep formation plugging;

[0054] (3) The profile control agent has a high plugging rate and strong plugging strength, meeting the long-term high-temperature flushing requirements of steam flooding;

[0055] (4) The profile control agent is used in the steam injection steam well profile control construction and has a significant oil production increase effect. During the construction operation, the deep profile control agent has a high plugging strength and can effectively plug the large pores and high permeability layers near the wellbore for a long time, with a significant production increase effect.

[0056] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0057] Table 1 Raw material components of profile control agent, the remainder is oilfield produced wastewater

[0058]

[0059] The preparation method of the profile control agent provided in Examples 1 to 3 is as follows: adding weighed thickener, crosslinker, heat stabilizer and cellulose ether to sewage, stirring for 20 minutes to obtain a mixture; adding the first plugging agent and the second plugging agent to the above mixture, stirring for 25 minutes to obtain a profile control agent.

[0060] Example 1

[0061] The profile control agent provided in Example 1 was tested in terms of initial viscosity, thermal stability and high-temperature plugging performance.

[0062] 1. Initial viscosity of profile control agent

[0063] The viscosity of the profile control agent was measured by a Brookfield viscometer. The results showed that the viscosity of the profile control agent just prepared was 168.2 mPa.s at room temperature (22°C) and 142.3 mPa.s at 50°C.

[0064] The above test results show that the profile control agent has a low initial viscosity, good pumpability, and is easy to enter deep formations. The viscosity will further decrease under high temperature formation conditions. Therefore, the profile control agent prepared in Example 1 has good injectability and is suitable for deep steam drive profile control operations.

[0065] 2. Thermal stability of profile control agent

[0066] The prepared profile control agent was placed in a 280°C oven for a long time at a constant temperature, and the gel strength was measured regularly. The viscosity of the profile control agent was above 37.6 Pa.s after aging for 15 days, above 33.2 Pa.s after 30 days, and above 31.8 Pa.s after 60 days.

[0067] The above test results show that the viscosity of the profile control agent generally decreases with time, but the reduction rate gradually decreases and tends to be stable. It has a strong plugging ability and can meet the requirement of steam drive for the viscosity of the profile control agent to be higher than 20Pa.s.

[0068] 3. Plugging performance test of profile control agent

[0069] The equipment used in the experiment includes: quartz sand (median particle size 0.15-0.30 mm), sand filling tube (Φ25 mm×500 mm), horizontal flow pump, pressure gauge, electronic balance, and profile control agent.

[0070] The experimental method is: vacuum the sand filling pipe, saturate it with water, measure the porosity and pore volume, and measure the water phase permeability after water drive until the pressure is stable; inject the profile control agent at an injection rate of 20mL / h, and stop injecting after the profile control agent fills the core; wait for 72 hours at 300℃, and inject clean water at an injection rate of 20mL / h until the core is broken through, and measure the breakthrough pressure. The test results are shown in Table 1.

[0071] Table 1 Plugging performance test results of profile control agent

[0072] Core number Original permeability (mD) Permeability after plugging (mD) Blockage rate (%) <![CDATA[Breakthrough pressure (Mpa.m -1 )]]> 1 1986 158 91.5 11.2 2 1597 114 92.8 12.3 3 1164 79 93.2 13.6

[0073] It can be seen from Table 1 that the profile control agent prepared in Example 1 can achieve a plugging rate of more than 90% under high temperature conditions of 300°C, and a plugging strength of more than 11.2 MPa / m, indicating that the profile control agent has the characteristics of high temperature resistance and high plugging strength, and has a good plugging effect on high permeability layers.

[0074] Example 2

[0075] The profile control agent provided in Example 2 was tested in terms of initial viscosity, thermal stability and high-temperature plugging performance.

[0076] 1. Initial viscosity of profile control agent

[0077] The viscosity of the profile control agent was measured by a Brookfield viscometer. The results showed that the viscosity of the profile control agent just prepared was 243.6 mPa.s at room temperature (22°C) and 224.3 mPa.s at 50°C.

[0078] The above test results show that the profile control agent has a low initial viscosity, good pumpability, and is easy to enter deep formations. The viscosity will further decrease under high temperature formation conditions. Therefore, the profile control agent prepared in Example 2 has good injectability and is suitable for deep steam drive profile control operations.

[0079] 2. Thermal stability of profile control agent

[0080] The prepared profile control agent was placed in a 280°C oven for a long time at a constant temperature, and the gel strength was measured regularly. The viscosity of the profile control agent was above 45.2 Pa.s after aging for 15 days, above 41.3 Pa.s after 30 days, and above 38.6 Pa.s after 60 days.

[0081] The above test results show that the viscosity of the profile control agent generally decreases with time, but the reduction rate gradually decreases and tends to be stable. It has a strong plugging ability and can meet the requirement of steam drive for the viscosity of the profile control agent to be higher than 20Pa.s.

[0082] 3. Plugging performance test of profile control agent

[0083] The equipment used in the experiment includes: quartz sand (median particle size 0.15-0.30 mm), sand filling tube (Φ25 mm×500 mm), horizontal flow pump, pressure gauge, electronic balance, and profile control agent.

[0084] The experimental method is: vacuum the sand filling pipe, saturate it with water, measure the porosity and pore volume, and measure the water phase permeability after water drive until the pressure is stable; inject the profile control agent at an injection rate of 20mL / h, and stop injecting after the profile control agent fills the core; wait for 72 hours at 300℃, and inject clean water at an injection rate of 20mL / h until the core is broken through, and measure the breakthrough pressure. The test results are shown in Table 2.

[0085] Table 2 Plugging performance test results of profile control agent

[0086] Core number <![CDATA[Original permeability (μm 2 )]]> <![CDATA[Permeability after plugging (μm 2 )]]> Blockage rate (%) <![CDATA[Breakthrough pressure (Mpa.m -1 )]]> 1 5218 461 91.2 13.1 2 4973 391 92.1 14.2 3 3129 263 91.6 13.8

[0087] It can be seen from Table 2 that the profile control agent prepared in Example 2 can achieve a plugging rate of more than 90% under high temperature conditions of 300°C, and a plugging strength of more than 13.1 MPa / m, indicating that the profile control agent has the characteristics of high temperature resistance and high plugging strength, and has a good plugging effect on high permeability layers.

[0088] Example 3

[0089] The profile control agent provided in Example 3 was tested in terms of initial viscosity, thermal stability and high-temperature plugging performance.

[0090] 1. Initial viscosity of profile control agent

[0091] The viscosity of the profile control agent was measured by a Brookfield viscometer. The results showed that the viscosity of the profile control agent just prepared was 183.2 mPa.s at room temperature (22°C) and 210.6 mPa.s at 50°C.

[0092] The above test results show that the profile control agent has a low initial viscosity, good pumpability, and is easy to enter deep formations. The viscosity will further decrease under high temperature formation conditions. Therefore, the profile control agent prepared in Example 3 has good injectability and is suitable for deep steam drive profile control operations.

[0093] 2. Thermal stability of profile control agent

[0094] The prepared profile control agent was placed in a 280°C oven for a long time at a constant temperature, and the gel strength was measured regularly. The viscosity of the profile control agent was above 43.1 Pa.s after aging for 15 days, above 40.5 Pa.s after 30 days, and above 39.8 Pa.s after 60 days.

[0095] The above test results show that the viscosity of the profile control agent generally decreases with time, but the reduction rate gradually decreases and tends to be stable. It has a strong plugging ability and can meet the requirement of steam drive for the viscosity of the profile control agent to be higher than 20Pa.s.

[0096] 3. Plugging performance test of profile control agent

[0097] The equipment used in the experiment includes: quartz sand (median particle size 0.15-0.30 mm), sand filling tube (Φ25 mm×500 mm), horizontal flow pump, pressure gauge, electronic balance, and profile control agent.

[0098] The experimental method is: vacuum the sand filling pipe, saturate it with water, measure the porosity and pore volume, and measure the water phase permeability after water drive until the pressure is stable; inject the profile control agent at an injection rate of 20mL / h, and stop injecting after the profile control agent fills the core; wait for 72 hours at 300℃, and inject clean water at an injection rate of 20mL / h until the core is broken through, and measure the breakthrough pressure. The test results are shown in Table 3.

[0099] Table 3 Plugging performance test results of profile control agent

[0100] Core number <![CDATA[Original permeability (μm 2 )]]> <![CDATA[Permeability after plugging (μm 2 )]]> Blockage rate (%) <![CDATA[Breakthrough pressure (Mpa.m -1 )]]> 1 4538 354 92.2 12.9 2 4762 372 92.2 13.5 3 3312 281 91.5 14.1

[0101] It can be seen from Table 3 that the profile control agent prepared in Example 3 can achieve a plugging rate of more than 90% under high temperature conditions of 300°C, and a plugging strength of more than 12.9 MPa / m, indicating that the profile control agent has the characteristics of high temperature resistance and high plugging strength, and has a good plugging effect on high permeability layers.

[0102] Comparative Example 1

[0103] Table 4 Raw material components of existing profile control agents, the remainder is oilfield produced wastewater

[0104]

[0105] The profile control agent provided in Comparative Example 1 was tested in terms of initial viscosity, thermal stability and high-temperature plugging performance.

[0106] 1. Initial viscosity of profile control agent

[0107] The viscosity of the profile control agent was measured by a Brookfield viscometer. The results showed that the viscosity of the profile control agent just prepared was 262.3 mPa.s at room temperature (22°C) and 231.2 mPa.s at 50°C.

[0108] The above test results show that the profile control agent has a low initial viscosity, good pumpability, and is easy to enter deep into the formation. The viscosity will further decrease under high temperature conditions of the formation. Therefore, the profile control agent prepared in Comparative Example 1 has good injectability.

[0109] 2. Thermal stability of profile control agent

[0110] The prepared profile control agent was placed in a 200°C oven for a long time at a constant temperature, and the gel strength was measured regularly. The viscosity of the profile control agent was above 3.1 Pa.s after aging for 5 days, above 4.5 mPa.s after 10 days, and above 3.8 mPa.s after 20 days.

[0111] The above test results show that the viscosity of the profile control agent decreases significantly with the extension of time, does not have long-term high temperature resistance, and cannot meet the requirements of steam drive for the viscosity of the profile control agent.

[0112] 3. Plugging performance test of profile control agent

[0113] The equipment used in the experiment includes: quartz sand (median particle size 0.15-0.30 mm), sand filling tube (Φ25 mm×500 mm), horizontal flow pump, pressure gauge, electronic balance, and profile control agent.

[0114] The experimental method is: vacuum the sand filling pipe, saturate it with water, measure the porosity and pore volume, and measure the water phase permeability after water drive until the pressure is stable; inject the profile control agent at an injection rate of 20mL / h, and stop injecting after the profile control agent fills the core; wait for 72 hours at 200℃, and inject clean water at an injection rate of 20mL / h until the core is broken through, and measure the breakthrough pressure. The test results are shown in Table 4.

[0115] Table 4 Plugging performance test results of profile control agent

[0116] Core number <![CDATA[Original permeability (μm 2 )]]> <![CDATA[Permeability after plugging (μm 2 )]]> Blockage rate (%) <![CDATA[Breakthrough pressure (Mpa.m -1 )]]> 1 4220 368 91.2 10.5 2 4160 391 90.6 10.1 3 3855 347 90.1 11.3

[0117] As can be seen from Table 4, the profile control agent prepared in Comparative Example 1 has a plugging rate of more than 90% under high temperature conditions of 200°C, and a plugging strength of more than 10.1 MPa / m, indicating that the profile control agent has a good plugging effect on the high permeability layer in the short term, but the gel cannot withstand high temperatures above 280°C for a long time and can only be used for temporary plugging, which cannot meet the long-term plugging requirements of steam injection wells.

[0118] Application of profile control agent provided in steam flooding production

[0119] The above-mentioned profile control agent is used in the profile control of the steam injection well of Qi 40 steam drive. The A25 well group was converted to steam drive development in December 2007, with steam injection in two layers. The thickness of the steam injection layer is 23.5m, with a total of 16 small layers. After long-term steam injection, the vertical steam absorption is seriously uneven, and the production effect of the corresponding oil wells gradually deteriorates. The oil production of the well group has dropped from 67.5 tons in the highest period to 21.8 tons. The comprehensive water content of the well group is as high as 88.4%, and the average temperature of the output fluid of the production well is 75.6℃. Two production wells need to be mixed with water to cool down in order to produce normally. In order to adjust the steam absorption profile of the steam injection well and inhibit the high-temperature steam channeling of the production well, the profile control agent prepared in Example 2 is used to implement profile control measures.

[0120] The specific construction process is as follows: Use the ground mixing tank to prepare the profile control agent, use the cement truck to mix the 600m 3 Profile control agent is injected into the formation at a low rate through the steam injection column, displacing 60m 3 The oil field produced wastewater and the well was sealed for 48 hours.

[0121] After the measures were taken, the steam injection pressure increased from 4.5MPa to 6.2MPa, an increase of 1.7MPa. After 30 days, the temperature monitoring of the observation well showed that the main layer temperature dropped by 36℃, the non-main layer temperature increased by 22℃, the wellhead temperature of the production well dropped by 9.3℃, the steam channeling layer was effectively blocked, and the vertical utilization degree was significantly improved; the average daily oil production of the well group increased from 21.8t to 36.6t, the daily liquid production decreased by 20.8t, the comprehensive water content decreased by 10.3 percentage points, the effective life period of the measures was 261d, and the cumulative oil production was 1,698t.

[0122] It can be seen from the above performance evaluation and field examples that the profile control agent provided in the examples of the present application has good injectability, good temperature resistance, high plugging strength, high plugging rate under high temperature conditions, and obvious oil-increasing effect in the profile control construction of steam-driven steam injection wells, and can be used in the profile control of steam injection wells in steam-driven oil reservoirs.

[0123] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A profile control agent, the raw material components of which include a first plugging agent, a thickener, a cross-linking agent and a thermal stabilizer, characterized in that: The raw material components also include cellulose ether and a second plugging agent; wherein, The raw material components of the second plugging agent include lignin fiber, starch and resin. The second plugging agent has a different particle size from the first plugging agent.

2. The profile control agent according to claim 1, characterized in that The cellulose ether includes the following: hydroxypropyl cellulose ether, hydroxyethyl cellulose ether, hydroxybutyl cellulose ether.

3. The profile control agent according to claim 1, characterized in that The resin includes one of the following: modified furfural resin and polyurethane.

4. The profile control agent according to claim 1, characterized in that The particle size of the second plugging agent is 1.5 mm to 3 mm.

5. The profile control agent according to claim 1, 3 or 4, characterized in that: The weight ratio of the lignin fiber, the starch and the resin is (55-65):(15-25):(15-25).

6. The profile control agent according to claim 1, characterized in that The particle size of the first plugging agent is 0.2 mm to 2 mm.

7. The profile control agent according to claim 1, characterized in that Calculated by mass fraction, the content of the cellulose ether is 1.0% to 1.5%.

8. The profile control agent according to claim 1, characterized in that: Calculated by mass fraction, the content of the second plugging agent is 2% to 3%.

9. The profile control agent according to claim 1, 7 or 8, characterized in that: In terms of mass fraction, the content of the first plugging agent is 6% to 8%, the content of the thickener is 0.2% to 0.3%, the content of the cross-linking agent is 0.2% to 0.3%, and the content of the heat stabilizer is 0.1% to 0.15%.

10. Use of the profile control agent according to claims 1 to 9 in steam flooding production.

Citation Information

Patent Citations

  • Environmental-friendly organic profile control agent and preparation method and use thereof

    CN104927816A

  • Biopolymer blends as emulsion stabilizers

    CN107484411A

  • No-residue fracturing fluid filtrate reducer of fractured reservoir, and de-filtration method

    CN108251096A

  • Water-based clay-free drilling fluid and application of drilling fluid to polar region frozen soil stratigraphical drilling

    CN110804424A

  • High-temperature profile control agent as well as preparation method and application thereof

    CN114479803A